Perioperative assessment for refractive cataract surgery. Issue 5 (May 2018) - Donaldson, Kendall; Fernández‐Vega‐Cueto, Luis; Davidson, Richard; Dhaliwal, Deepinder; Hamilton, Rex; Jackson, Mitchell; Patterson, Larry; Stonecipher, Karl
Abstract : N/A: As cataract surgery has evolved into lens‐based refractive surgery, expectations for refractive outcomes continue to increase. During the past decade, advancements in technology have provided new ways to measure the cornea in preparation for cataract surgery. The increasing ability to accurately estimate corneal power allows determination of the most precise intraocular lens (IOL) for each patient. New equipment measures the anterior and posterior corneal surfaces to most accurately estimate corneal power and corneal aberrations. These measurements help surgeons make the best decisions regarding the power of the IOL to be implanted during cataract surgery. However, with all the available technology, it can be difficult to decipher which of the many technologies is necessary or best for patients and for practices. This article reviews currently available options for topography, tomography, keratometry, and biometry in preparation for cataract surgery. In addition, intraoperative aberrometry and integrated cataract suites are reviewed.